Effect of Spent Lubricating Oil on Some Growth Parameters of Two Varieties (TGXl485 - ID and TGXl448 - 2E) of Soybeans, (Glyzine max. merril) (2002)
The effects of spent lubricating oil on the growth of two varieties of soybean (TG x 1485-ID; (V1)) and (TG x 1448-2E; (V2)) were investigated in the laboratory and greenhouse experiments. In all the plants treated with spent lubricating oil, germination was delayed when compared with the Controls. Also results from growth parameters such as stem height/plant, number of leaves/plants, - number of nodes/plants and number of branches/plant indicated that spent lubricating oil had some adverse effects on the growth of soybeans. However, V1 seems to be more tolerant to contamination by spent lubricating oil in terms of growth indices than V2, which suffered most. Generally, while V2 produced a net higher dry pod weight/plant, V1 produced less dry weight/plant. It was generally observed in the study that with increasing level of oil contamination, the toxicity of the oil was more pronounced